The absorption of glycosaminoglycans of different molecular weight obtained from Apostichopus japonicus: an in vitro and in situ study. Issue 12 (18th May 2021) - Ma, Mengjie; Wang, Han; Yuan, Yongkai; Wang, Yuanhong; Yang, Shuang; Lv, Zhihua
Abstract : The purpose of this study was to investigate the absorption and transport of glycosaminoglycan from Apostichopus japonicus (AHG) and its depolymerized derivatives (DAHG-1, DAHG-2, DAHG-3). Abstract : The purpose of this study was to investigate the absorption and transport of glycosaminoglycan from Apostichopus japonicus (AHG) and its depolymerized derivatives (DAHG-1, DAHG-2, DAHG-3). The AHG and depolymerized AHGs (DAHGs) were characterized by high-performance gel permeation chromatography (HPGPC), Raman spectroscopy and atomic force microscopy (AFM). The results showed that there was no significant difference of an AHG primary structure and functional groups during the depolymerization. Meanwhile, AFM observation showed that AHG and DAHGs possessed linear structures. In this study, a rapid and sensitive liquid chromatographic post-column derivatization method was used to investigate the absorption of AHG and DAHGs with the Caco-2 cell model, the M cell model and the intestinal recirculating perfusion. It was found that AHG and DAHGs can be absorbed in the intestine, and their transport involved endocytosis.